The Development of Learning Text Using Max Oxborn’s Little Prince: Preservice English Teachers’ Points of Views - Arina Risqonah; Dwi Agustina (Universitas Muhammadiyah Semarang, 2022)
Finding out a text which is appropriate to students’ needs is sometimes not easy. In the pandemic era, however, teachers are required to present texts which are more interesting for students’ learning, especially because the learning is done online. Without the presentation of interesting texts, students may get bored to read during their online learning. In order for the teachers to be able to present interesting texts, previous studies have shown that teachers can develop a learning text from movies or films. Referring to the previous studies, the writers were interested to develop English text material using the film Little Prince by Max Oxborn as the learning media and investigate how pre-service English teachers perceived it as a learning text for senior high schools. The research was done by using Borg and Gall’s model in which the writers followed were five stages namely initial data collection, planning, initial product format development, initial product testing (in a small scale), and the revision of the product. In this article the writers present the learning text created from the film Max Oxborn’s Little Prince along with how pre-service English teachers perceived the text produced in this research as a learning material.